New eyes on the universe : twelve cosmic mysteries and the tools we need to solve them - Webb, Stephen (Springer Praxis Books, 2012)
Today's scientists have at their command a wide range of sensitive and powerful instruments, not only those that capture electromagnetic radiation but also 'telescopes' for cosmic rays, neutrinos, gravitational waves, and dark matter. Using the vast amount of observational data produced by this new generation of observatories and telescopes, New Eyes on the Universe shows how some of the outstanding puzzles inherent in our emerging world view might be solved. With color illustrations throughout the text, this book is a fascinating exploration of the mysteries that the Universe still contains, such as - What is causing the Universe to blow itself apart? - What could be powering the luminous gamma-ray bursters? - Where is all the matter in the Universe? - Do other Earths exist? - What is the nature of dark matter? New Eyes on the Universe looks at these and other key issues in modern astronomy and cosmology. It explains clearly, without recourse to mathematics, why each question is puzzling and worthy of research.